Entre o visível e o invisível: um estudo sobre as congadas da Lapa- PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This work aims to contribute to the construction of a new perspective on the Congadas in the city of Lapa - PR, recognizing them as an integral part of the Lapean cultural heritage. For this purpose, a bibliographic review was made on cultural history, heritage education and oral history as a methodological option, to elaborate a narrative with reports from local residents, participants and people directly or indirectly linked to Congadas. There is a discussion about the formation of Paraná society and its identity elements, in dialogue with sources related to cultural identity with Stuart Hall, inventions of practices and daily life with Hobsbawn, in addition to dialogue with Pollack about the selection of memories. In this context, a reflection on cultural heritage is presented, teaching History and heritage education. Based on the reconstruction of the history and the importance of the Congadas, reworked from the memory of its participants, and from the recognition as a part of the cultural heritage from Lapa-Pr, a material and immaterial cultural asset, it is proposed among the countless possibilities of didactic and/ or paradidactic work, the production of an alternative itinerary to visit the city of Lapa, containing new perspectives on elements about the black presence in history and Lapean society, which today are “invisible”, contributing to a new view at the cultural manifestations present in the city, as well as the elaboration of an e-book containing, in addition to the alternative script, information about Congadas and Afro culture in the state of Paraná, with the purpose of subsidizing the work of teachers in the history teaching and others agents in the patrimonial education work.
Keywords: Congada; Educação Patrimonial; História Cultural; História Oral; Lapa; Congada; Lapa; Cultural History; Patrimonial Education; Oral History; CNPQ::CIENCIAS HUMANAS::HISTORIA